Growth and Convergence across the US: Evidence from County-Level Data - Matthew J. Higgins; Daniel Levy; Andrew T. Young (Bar-Ilan University, Department of Economics, 2005)
We use U.S. county data (3,058 observations) and 41 conditioning variables to study growth and convergence. Using OLS and 3SLS-IV we report on the full sample and metro, non-metro, and 5 regional samples: (1) OLS yields convergence rates around 2 percent; 3SLS yields 6–8 percent; (2) convergence rates vary (e.g., the Southern rate is 2.5 times the Northeastern rate); (3) federal, state and local government negatively correlates with growth; (4) the relationship between educational attainment and growth is nonlinear; and (5) finance, insurance & real estate industry and entertainment industry positively correlates with growth while education employment negatively correlates.
Keywords: O40; O11; O18; O51; R11; H50; H70; 330; Economic Growth; Conditional Convergence; and County-Level Data